Identificação e avaliação de compostos bioativos de capim-annoni em plantas daninhas - Favaretto, Adriana (2018)
Allelopathic plants, such as tough lovegrass (Eragrostis plana), can be used to control weeds by supplying bioactive compounds with phytotoxic activity. This work aimed to test if the tough lovegrass has herbicide potential, by means of three experiments. Experiment 1: the separated and joint phytotoxicity of the catechin, epicatechin and the caffeic, ferulic, p-coumaric and vanillic acids, identified in the tough lovegrass, were tested on lettuce (Lactuca sativa) seeds and seedlings. All compounds were phytotoxic, especially on seedlings. Only vanillic acid was phytotoxic on seed germination. Catechin and epicatechin did not act together, caffeic acid potentialized p-coumaric acid activity and caffeic and ferulic acids were antagonistic. Experiment 2: the fractionation of ethanolic extracts from tough lovegrass leaves resulted in the hexane, dichloromethane, ethyl acetate, butanol and hydroethanolic fractions, which were later used to perform germination and initial growth bioassays with horseweed (Conyza canadensis), sourgrass (Digitaria insularis), hairy beggarticks (Bidens pilosa) and lettuce. The phytotoxicity of the fractions was observed both on germination and on initial growth of the tested plants. The hexane and dichloromethane fractions were the most phytotoxic and lettuce and sourgrass were the most susceptible plants. Experiment 3: bioguided fractionation allowed the isolation and identification of three diterpenes previously unknown in tough lovegrass roots. These compounds inhibited the growth of duckweed (Lemna paucicostata), with IC50 values of 109, 200 and 59 μM, respectively. The α-linolenic acid was identified in leaves of tough lovegrass and caused necrosis in duckweed at 10 μM. The results indicate that the allelochemicals from tough lovegrass act both jointly and in separate. They are present in the hexane, dichloromethane, ethyl acetate, butanol and hydroethanolic fractions. Compounds isolated for the first time in tough lovegrass should be tested for herbicide potential.